A Comparison of Antecedents of Different Types of Innovation – V - Glor, Eleanor D (Innovation Journal, 2021)
Antecedents of innovation precede their implementation and probably influence which innovations and whether they are approved and implemented. Antecedents have been identified in a considerable number of types of innovation. Are they the same in these types? A systematic literature review (SLR) of antecedents of policy innovation found 594 antecedents, 508 of them unique, in 87 articles on trailblazing and adoption. So many antecedents suggest a lack of clarity about what the antecedents of policy innovation may be. They have been clarified for policy innovation. In this paper the antecedents of policy innovation are compared to antecedents of private, public sector and social innovation identified in literature reviews, SLRs and metaanalyses to see whether common or different antecedents are identified in these literatures. While the literature often implies antecedents of different types of innovation are the same by lumping them together, they were found to vary somewhat by type of innovation, especially trailblazing and higher-level factors and clusters. External antecedents were only found to be important for policy innovation and dissemination; political antecedents were particularly important for trailblazing; internal antecedents were important for all types of innovation. Literature on antecedents of private innovations did not consider external or political antecedents. Four research questions are addressed: Q. 1: At what level should antecedents of innovation be analyzed and compared? Q. 2: How do antecedents identified for different types of innovation compare—private, public and public-social sectors? Q. 3: How do clusters identified for different types of public sector innovation compare— processes; trailblazing and adoption of policy; dissemination; private, public, public-social sectors? Q. 4: Do a common set of unique and grouped antecedents, factors and clusters influence all types of innovation equally or are their antecedents discernably different? Key words: antecedents of innovation, comparison of antecedents, types of innovation, systematic literature review.
Number: 2